BOTH SIDES OF THE FENCE: METHODOLOGICAL CHALLENGES IN UNDERTAKING RESEARCH INTO END OF LIFE CARE FOR PRISONERS. Issue 1 (1st March 2014) - Turner, M; Peacock, M; Froggatt, K; Payne, S; Fletcher, A; Gibson, R; Scott, G
Abstract : Introduction: The number of older prisoners in the UK has more than doubled in the last decade, with the greatest increases amongst those over 70. Around 40% of older prisoners are sex offenders, many of whom are in prison for the first time due to historic abuse. Longer sentences and more stringent release criteria mean that increasing numbers of anticipated deaths in prison are predicted. Prison staff experience tensions between care and custody and demands for considerable emotional labour in delivering palliative care to such prisoners. Aim(s) and method(s): This paper presents some of the methodological challenges encountered during the early stages of the 'Both sides of the fence' study, which uses action research to develop a transferable model of integrated palliative care for prisoners. The first phase comprises a detailed situational analysis to explore current palliative care provision in one prison; then healthcare and custodial staff participate in action cycles to implement and evaluate changes to practice. Results: A prison with a large population of older and disabled prisoners was identified as the research site, and access was granted following ethical and governance approvals. Engagement of diverse groups of staff in the research required multiple meetings, extensive networking and the visible on-site presence of the researcher; this engagement led to an important protocol amendment to include focus groups with prisoners who provide informal care to fellow prisoners. Conclusion(s): Establishing effective connections with a wide range of prison staff has been key to overcoming the methodological challenges and progressing the research.